Clinical Manifestation and Mutation Spectrum of 53 Unrelated Pedigrees with Protein S Deficiency in China - Li, Lei; Wu, Xi; Wu, Wenman; Ding, Qiulan; Cai, Xiaohong; Wang, Xuefeng (Thrombosis and Haemostasis, 2019)
Protein S (PS) deficiency is associated with a 10-fold increased risk of venous thromboembolism (VTE), but its diagnosis is quite difficult and complicated. In this study, we identified 53 unrelated pedigrees with PS deficiency in China. Data of their clinical characteristics and laboratory examinations were collected. Genetic analysis of PROS1 including direct sequencing, copy number variant detection and messenger ribonucleic acid analysis was performed in probands and related family members. Of these 53 probands, 52.8% (28/53) experienced multi-site and/or recurrent thrombotic episodes, mainly manifested as deep venous thrombosis and/or pulmonary embolism (82.7%). Additional risk factors of VTE were observed in 39.6% (21/53) probands who exhibited a significantly higher rate of recurrent VTE compared with those not, in which 7 probands were complicated by anti-phospholipid syndrome. Most probands and family members exhibited quantitative PS deficiency with impairment of both activated protein C and tissue factor pathway inhibitor cofactor activities. Note that 87.2% (34/39) PROS1 detectable mutation rate was obtained through comprehensive phenotypic and genetic analysis. A total of 36 PROS1 causative mutations including 16 novel mutations were identified in 48 probands, whereas no PROS1 mutations were detected in the other 5 probands. Three hotspot mutations (Glu67Ala, Arg561Trp and Tyr560*) were identified in the Chinese population for the first time. This article provides a framework for correlating the clinical pathogenesis of PS deficiency to genetic backgrounds in the Chinese population.
Keywords: protein S deficiency; PROS1; mutation spectrum; venous thromboembolism